Influencing Factors in Psychological Resilience: A Study on the Role of Emotional Reassurance and Optimism as Predictive Dimensions - Alhemaidi Mohammed Aldhaidan (LED Edizioni Universitarie, 2020)
The present study aims to investigate the relative contribution of emotional reassurance and optimism in predicting psychological resilience in secondary school students. A total of 265 senior secondary student's male participated in this study. Participants' ages ranged from 16 to 18. Instruments measuring emotional reassurance, optimism, and psychological resilience, were administered to senior secondary students in Quranic Memorization Schools (QMSs). The researcher used the Pearson correlation coefficient and multiple regression analysis technique. The findings indicated that there was a positive correlation between psychological resilience and emotional reassurance among the students on the level of 0.01. Furthermore, the findings indicated that there was a positive correlation between psychological resilience and optimism among the sample on the level of 0.01. Finally, the findings also showed that the emotional reassurance and optimism contributed statistically significant in the prediction of psychological resilience among secondary school students. Therefore, academic counsellors, teachers, school principals, and parents should develop optimism, emotional reassurance and psychological resilience, self-esteem in their students and children in the early years.